(3GdCTHGg hGdfXGFQ GdfMhjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3efUhQ Hf MSf GdNhGfcj GdTGaYj s)
(3ChdgG (B:s
(3CeG HYO, aEf afhf GdYQHjI Ydi GNJdGa CfhGYgG gj Chd afhfj heHJOC GdCNHGQ cGf aj CMGOjKgG SeQj hTLhfj s
(3BNQgG (B:s
(3aj WGQFg Ydjg bWYkG, hJhLH LQ ZjQ GdefUQa LRekG cedJ GdCTHGg hGdfXGFQ GdfMhjI HMeO Gddg s
(3fSNI KGfjI JJab aj ChdgG eY Chd GdfSNI GdChdi JeGekG hcPdc BNQgG HGNJdGa jSjQ aj HYV GdCdaGXs
(3hgj fSNI fbdJ ef fSNI efbhdI ef NW GdeDdas
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs